Microzooplankton Communities in a Changing Ocean: A Risk Assessment - López Abbate, María Celeste (2021)
Microzooplankton communities are fundamental components of marine food webs and have the potential to impact the functioning of carbon pumps. The identification of common responses of microzooplankton to global change has been challenging due to their plasticity and complex community-level interactions. However, accumulating research is providing new insights on the vulnerability of this group to different climate and other human-related hazards. Here, the current and future risk levels of microzooplankton associated with global change are assessed by identifying prevailing hazards, exposure, sensitivity, natural adaptability, and observed impacts based on available evidence. Most documented hazards for the survival and yield of microzooplankton are ocean warming, acidification, deoxygenation, and coastal eutrophication. Overall, heterotrophic protists are expected to respond and adapt rapidly to global trends. Fast growing, mixotrophy, wide internal stoichiometry, and their capacity to track optimal environmental conditions by changing species? range distribution are among the most important traits that shape their high adaptability to global change. Community-level responses to warming, however, are predicted to be amplified in polar and subpolar regions. At the individual level, the highest risk is associated with the sensitivity to deoxygenation since microzooplankton, especially ciliates, are known to reduce metabolic rates under hypoxic episodes; however, vulnerable species can be readily replaced by specialized taxa from a similar functional type. Microzooplankton seem to act as functional buffers of environmental threats, thus conferring stability, in terms of community connectedness to marine food webs and ecosystems against external disturbances.